Unexpected Heartbreak: Takotsubo Cardiomyopathy Induced by Esophagogastroduodenoscopy - Wassim Abouzeid, MD; Ahmad Haddad, MD; Mohammad Kloub, MD; Yazeed Abu Ruman, MD; Kinjal Patel, MD; Joaquim Correia, MD (Texas Heart Institute Journal)
Takotsubo cardiomyopathy (stress cardiomyopathy, or broken-heart syndrome), characterized by reversible left ventricular dysfunction without clinically significant coronary artery obstruction, is rare but has been more commonly reported recently. Esophagogastroduodenoscopy as a cause of takotsubo cardiomyopathy remains exceedingly rare. The case report of an 84-year-old female patient with a complex medical history who had acute stress cardiomyopathy following esophagogastroduodenoscopy, which required prolonged hospitalization and hemodynamic support, is presented. This case emphasizes the importance of recognizing and considering this uncommon pathology and its complications in differential diagnosis. Diagnostic modalities and treatment options for this condition are also discussed.